Do Shariah-compliant Companies Engage Lesser Earnings Management Behaviour? - Mohd Sabrun, Ibrahim; Muhamad, Rusnah; Yusoff, Haslinda; Darus, Faizah (Asian Journal of Business and Accounting, 2018)
Manuscript type: Research paper. Research aims: This study aims to understand how reputation, finan- cial distress and financial performance influence Shariah-compliant companies into engaging earnings management behaviour. The financial data of 69 FTSE Bursa Malaysia 100 Index companies, dating 2010 to 2014 (five years), were analysed. Design/ Methodology/ Approach: This study uses the Modified Jones model (Jones, 1991; Dechow, Sloan, & Sweeney, 1996), Roychow- dhury’s model (2006) to examine earnings management behaviour of Shariah-compliant companies. Research findings: The results of this study suggest that company’s reputation, financial distress and financial performance are factors that can influence company’s earnings management behaviour and that Shariah values are ineffective in deterring the management from earnings management behaviour. Theoretical contribution/ Originality: The findings of this study contribute to the literature by showing that Shariah values may not be beneficial in shaping good business management and reporting practices. Practitioner/ Policy implications: The alarming results drawn from this study is a reason for policy setters and relevant accounting bodies to give more emphasis on developing better accounting and reporting policies. Research limitation: This study is limited to non-financial sectors due to measurement limitations. Keywords: Earnings Management, Financial Distress, Financial Per- formance, Fraud Diamond Theory, Reputation, Shariah-compliant JEL Classification: M41